Macierzyństwo zastępcze - przegląd prawnoporównawczy - Silva-Ruiz, Pedro F. (Wydział Prawa i Administracji UAM, 1991)
The topic of the paper is surrogate motherhood or the application of artificial conception techniques - artificial insemination or fertilization in vitro - whereby one woman carries a child for another with the intention that the child be handed over after birth. Surrogacy raises both ethical and legal issues. Thus, surrogacy for convenience alone, that is where a woman is physically capable of bearing a child but does not wish to undergo pregnancy, is considered as ethically unacceptable. Even in compelling medical circumstances the danger of exploitation of one human being by another appears far too outweigh the potential benefits, in almost every case. Among the many legal issues raised by surrogate motherhood, the paper studies two, namely: 1) the constitutional question of the right to procreate and its scope, particularly in the United States, 2) the issue of the validity of the contract of surrogate motherhood.
Surrogate motherhood: a comparative law overview